Green accounting and ESG-driven eco-efficiency in European financial institutions: A two-stage DEA–CRITIC-TOPSIS evaluation - George Sklavos; Georgia Zournatzidou; Konstantina Ragazou; Nikolaos Sariannidis (PLoS ONE, 2025)
Background Evaluation of the eco-efficiency of financial institutions and their underlying green accounting practices is imperative as Environmental, Social, and Governance (ESG) principles become ingrained in financial regulation and investment strategy. Nevertheless, the current ESG assessments frequently suffer from a lack of a dual focus on governance quality and performance, which raises concerns about misaligned reporting and Greenwashing. Objective This investigation suggests a two-stage methodological framework for evaluating the eco-efficiency of European financial institutions that is driven by ESG and evaluating the impact of internal green accounting practices on sustainability performance. Methods Data Envelopment Analysis (DEA) is implemented in the initial phase to calculate eco-efficiency scores that are determined by financial outputs and environmental inputs (GHG emissions, energy consumption, assets). The second stage employs the CRITIC-TOPSIS method to rank 365 institutions according to seven governance-related green accounting criteria. These criteria are derived from the Refinitiv ESG Screener CO₂ dataset. The performance frontiers are identified by DEA, while the contribution of internal sustainability mechanisms is assessed by CRITIC-TOPSIS. Results According to the DEA results, only 38% of institutions are entirely efficient, with a substantial degree of variation across the sample. The results of the CRITIC-TOPSIS analysis indicate that the most reliable predictors of green accounting quality are governance indicators, including the presence of an ESG committee and board supervision of climate risks. According to a moderate positive correlation between DEA scores and TOPSIS rankings, eco-efficiency and green accounting maturity are related, but they are not entirely aligned. Conclusions The results underscore the importance of integrating institutional governance evaluations with operational performance metrics to accurately evaluate sustainability. Theoretical and methodological contributions to the disciplines of environmental accounting and sustainable finance are made by this integrated framework, which provides regulators, rating agencies, and institutional decision-makers with valuable insights.